ALCOHOL LEVELS IN CEREBROSPINAL-FLUID AND BLOOD-SAMPLES FROM PATIENTS UNDER PATHOLOGICAL CONDITIONS - Agapejev, S.; VASSILIEFF, I; Curi, P. R. (Munksgaard Int Publ Ltd, 1992)
We measured alcohol levels by the Cordebard method in 148 CSF samples from individuals who had abstained from alcohol for at least 7 days prior to the beginning of the study. Each blood sample was accompanied by a CSF sample from the same patient. CSF samples found to be normal after analysis were used as controls. Mean alcohol concentration in blood did not differ significantly between the control group and the groups with altered CSF. The group with altered CSF had statistically higher alcohol levels in CSF than in blood. CSF lactate, glucose and protein levels were not correlated with alcohol level. The results suggest the presence of endogenous alcohol in the CSF, with levels increasing in the presence of pathological processes involving the nervous system.
Keywords: CEREBROSPINAL FLUID; BLOOD; ALCOHOL; CORDEBARD METHOD